Greenhouse growth of Cayman and Cobra grasses under diverse NaCl salinity levels - Sánchez-Bernal, Edgar Iván; Santos-Jerónimo, Silvia; Ortega-Escobar, Héctor Manuel; López-Garrido, Serafín Jacobo; Camacho-Escobar, Marco Antonio (REVISTA TERRA LATINOAMERICANA, 2020)
Saline soils affect the growth and yield of pastures and decrease the availability of forage for animal feed. Objective: To evaluate the emergence, growth and biomass production of the Cayman (BR/1752) and Cobra (BR/1794) grasses under salinity conditions induced by NaCl salt at seven levels of electrical conductivity (CE) of 0, 2, 4, 6, 10, 12 and 15 dS m-1. Methodology: In a greenhouse, experimental pots with agrolite were planted at a density of 25 seeds per pot, to evaluate emergence. Later a clear was performed to leave three plants per pot in a completely random design. Irrigation consisted of replacing the water lost through evaporation by supplying distilled water. The experiment covered a period of 60 days, during which the height of plants, diameter of stem, number of shoots, number of leaves, root length and biomass production were determined. The results indicate that increasing the concentration of NaCl for both pastures, differentially decreased the percentage of emergence, height of plants, stem diameter, the number of shoots and the number of leaves and consequently these reductions affected the biomass production of the plants. The degrowth was more pronounced in Cayman grass than in Cobra grass. Cultivars showed tolerance differences since in the Cayman grass biomass production was signif icantly affected (P = 0.05) at CE ≥ 10 dS m-1, while in Cobra grass this decrease occurred at CE ≥ 12 dS m-1.